Revitalisasi Fungsi Teologi Islam dalam Konteks Multikultural Perspektif Fethullah Gulen - Muhammad Said (LPPM IAIN Sultan Amai Gorontalo, 2016)
This article describes on the neccesity of renewal Islamic theology within context of pluralism and multiculturalism society. One of the contemporary Muslim scholars, Fethullah Gulen, could be considered among the most influential Muslim theologians of our time. His work focus on redefining the nature of Islamic discourse in the contemporary world by doing interreligious and intercultural dialogue. Nowdays, we need to shift our paradigm from classical kalam which dogmatic, abstract, and exclusive to more practical theology based on contemporary life needs, which is called “social theology”. Gulen’s theological discourse distinguished for his support of democracy, humanism, openness to globalization, progressiveness in integrating tradition with modernity, and to make sense of pluralistic-piety.